Implementation of “Pecel Jawara Madiun” in Character Education through Holistic Approach to Elementary School Learners - Desita Anggi Harumsari; Winarno Winarno; Joko Daryanto (Universitas Sebelas Maret, 2024)
This research describes the implementation of